Nanophytomedicines for the Prevention of Metabolic Syndrome: A Pharmacological and Biopharmaceutical Review - Nouri, Zeinab; Hajialyani, Marziyeh; Izadi, Zhila; Bahramsoltani, Roodabeh; Farzaei, Mohammad Hosein; Abdollahi, Mohammad (Frontiers in Bioengineering and Biotechnology, 2020)
Metabolic syndrome (MetS) includes a series of metabolic abnormalities that leads to diabetes mellitus and cardiovascular diseases. Plant extracts, due to their unique advantages like anti-inflammatory, antioxidant, and insulin sensitizing properties, are interesting therapeutic options to manage MetS; however, the poor solubility and low bioavailability of lipophilic bioactive components in the herbal extracts are two critical challenges. Nano-scale delivery systems are suitable to improve delivery of herbal extracts. This review, for the first time, focuses on nanoformulations of herbal extracts in MetS and related complications. Included studies showed that several forms of nano drug delivery systems such as nanoemulsions, solid lipid nanoparticles, nanobiocomposites, and green-synthesized silver, gold, and zinc oxide nanoparticles have been developed using herbal extracts. It was shown that the method of preparation and related parameters such as temperature and type of polymer are important factors affecting physicochemical stability and therapeutic activity of the final product. Many of these formulations could successfully decrease the lipid profile, inflammation, oxidative damage, and insulin resistance in in vitro and in vivo models of MetS-related complications. Further studies are still needed to confirm the safety and efficacy of these novel herbal formulations for clinical application.